Analisis Proses Produksi Dengan Value Stream Mapping Pada Industri Manufaktur - Brilianto, Rafi; Waluyowati, Nur Prima (Jurnal Kewirausahaan dan Inovasi, 2024)
Lean manufacturing is one of the concepts used as a strategy by manufacturing companies to remain competitive in the industry by reducing the seven wastes. PT Trafoindo Prima Perkasa is one such manufacturing company that produces electrical instruments such as transformers and is currently working on reducing waste. This research aims to identify the waste occurring in the production line of dry-type transformers, the activities causing waste, and efforts to minimize it. This type of research is exploratory, describing the phenomenon of waste in the production line of dry-type transformers. The research uses the value stream mapping (VSM) method with the value stream analysis tools (VALSAT) and process activity mapping (PAM). Based on the research results, the waste that occurs includes transportation (23.88%), motion (21.64%), waiting (18.65%), inventory (10.44%), defects (8.96%), over-processing (8.71%), and over-production (7.72%). The current state mapping shows a production lead time of 13 days 5 hours with a processing time of 68 hours and 8 minutes. After implementing recommendations to minimize waste, the future state mapping shows a reduction in the production lead time to 10 days and 5 hours and a reduction in processing time to 51 hours and 1 minute.   Abstrak Lean manufacturing merupakan salah satu konsep yang digunakan sebagai strategi perusahaan manufaktur agar tetap exist di persaingan industri dengan cara mengurangi 7 (tujuh) pemborosan (seven waste). PT Trafoindo Prima Perkasa merupakan salah satu perusahaan industri manufaktur instrumen listrik berupa trafo yang sedang berusaha mengurangi pemborosan. Penelitian ini bertujuan untuk mengetahui proses produksi yang terjadi di production line dry type transformer sudah optimal atau belum dan upaya upaya perbaikan untuk meminimasi pemborosan. Jenis penelitian ini merupakan exploratory research yang menjelaskan mengenai fenomena pemborosan terjadi di production line dry type transformer. Penelitian ini menggunakan metode value stream mapping (VSM) dengan alat analisis value stream analysis tools (VALSAT) dan process activity mapping (PAM). Berdasarkan hasil penelitian, pemborosan yang terjadi berupa transportation (23,88%), motion (21,64%), waiting (18,65%), inventory (10,44%), defect (8,96%), over-processing (8,71%), dan over-production (7,72%). Current state mapping menunjukkan jumlah production lead time selama 13 hari 5 jam dengan processing time selama 68 jam lebih 8 menit. Adapun setelah dilakukan rekomendasi perbaikan dengan meminimasi adanya pemborosan, hasil future state mapping menunjukkan adanya pengurangan jumlah production lead time menjadi 10 hari lebih 5 jam dan pengurangan jumlah processing time menjadi 51 jam lebih 1 menit.